Prospects for constraining light-quark electroweak couplings at Higgs factories - Mękała Krzysztof; Jeans Daniel; Reuter Jürgen; Tian Junping; Żarnecki Aleksander Filip (EPJ Web of Conferences)
Electroweak Precision Measurements are stringent tests of the Standard Model and sensitive probes to New Physics. Accurate studies of the Z-boson couplings to the first-generation quarks could reveal potential discrepancies between the fundamental theory and experimental data. Future e+e− colliders running at the Z-pole and around the ZH threshold would be an excellent tool to perform such a measurement, unlike the LHC where hadronic Z decays are only available in boosted topologies. The measurement is based on comparison of radiative and non-radiative hadronic decays. Due to the difference in quark charge, the relative contribution of the events with final-state radiation (FSR) directly reflects the ratio of decays involving up-and down-type quarks. Such an analysis requires proper modeling and statistical discrimination between photons coming from different sources, including initial-state radiation (ISR), FSR, parton showers and hadronisation. In our contribution, we show how to extract the values of the Z couplings to light quarks and present the estimated uncertainties of the measurement.